Correlation Between Platelet and Hematocrite Values with Duration Fever in Dengue Hemorrhagic Fever (DHF) Patients at Dr. Soedomo General Hospital, Trenggalek - Alelo, Richardo Reynaldi Sakka; Sucipto, Teguh Hari; Soegijanto, Soegeng; Wardhani, Puspa (Indonesian Journal of Tropical and Infectious Disease, 2025)
Dengue Hemorrhagic Fever (DHF) is an endemic disease in Indonesia with laboratory manifestations such as thrombocytopenia and hemoconcentration. The duration of fever in DHF can be an indicator of disease severity, but its relationship to laboratory parameters such as platelets and hematocrit requires further study. The purpose of this research is to determine the relationship between platelet and hematocrit values and the duration of fever in DHF patients at Dr. Soedomo Trenggalek Regional General Hospital. This study used a cross-sectional design with secondary data from the medical records of 71 dengue fever patients. Statistical analysis used the Spearman correlation test to assess the relationship between platelets and hematocrit with fever duration. 54.93 % of patients were male, with the largest age group being young adults (26–45 years, 39.44%). The maximum duration of fever was 5 days (54.93 %). There was a weakly significant relationship between decreased platelets and increased duration of fever (p = 0.025; r = 0.266). However, there was no significant relationship between hematocrit and duration of fever (p = 0.359; r = -0.111). Platelets can be used as an indicator to estimate the duration of fever in dengue fever patients, while hematocrit did not show a significant relationship. These findings support the importance of platelet monitoring for the clinical management of dengue fever, although factors such as fluid therapy and disease phase need to be considered in hematocrit interpretation.